2014
DOI: 10.1016/j.mri.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing reproducibility of diffusion-weighted magnetic resonance imaging studies in a murine model of HER2+ breast cancer

Abstract: Background and purpose The use of diffusion-weighted magnetic resonance imaging (DW-MRI) as a surrogate biomarker of response in preclinical studies is increasing. However, before a biomarker can be reliably employed to assess treatment response, the reproducibility of the technique must be established. There is a paucity of literature that quantifies the reproducibility of DW-MRI in preclinical studies; thus, the purpose of this study was to investigate DW-MRI reproducibility in a murine model of HER2+ breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…71 Similarly, Whisenant et al reported a wCV of 12.0% and 95% CI of 11.8% for a metric extracted from repeated diffusion weighted MRI (DW-MRI) scans. 65 As our animal model is similar to these studies, the MIE elasticity biomarker is shown to exhibit a precision similar to DCE-MRI and DW-MRI analyses.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…71 Similarly, Whisenant et al reported a wCV of 12.0% and 95% CI of 11.8% for a metric extracted from repeated diffusion weighted MRI (DW-MRI) scans. 65 As our animal model is similar to these studies, the MIE elasticity biomarker is shown to exhibit a precision similar to DCE-MRI and DW-MRI analyses.…”
Section: Discussionsupporting
confidence: 62%
“…70 Our results are also in agreement with reproducibility analysis for other types of quantitative MRI data previously reported. 65,[71][72][73] In a similar mouse model of breast cancer, Barnes et al reported wCVs from 8.3 to 15.6% and 95% CIs from 7.5 to 14.3% for metrics extracted from standard pharmacokinetic analysis of dynamic contrast enhanced MRI (DCE-MRI) data over the tumor region of interest for repeat scans. 71 Similarly, Whisenant et al reported a wCV of 12.0% and 95% CI of 11.8% for a metric extracted from repeated diffusion weighted MRI (DW-MRI) scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in ADC was reported as a reproducible good index for efficient cancer therapy, which is directly related to the number of killed tumor cells and thought to be due to the liberation of water into the extracellular space as a result of cell necrosis. 17 Interestingly, the iron oxide nanoparticles presented in SWCNT⋅ + CD105 + DOX samples, which were found to express an attenuation in T2* once reaching the tumor site, produced a transient decrease in ADC at 2 hours post-administration, due to the disturbance of …”
Section: Discussionmentioning
confidence: 99%
“…MRI has the superiority of simultaneously offering both anatomical (ie, using standard spin-echo sequence) and early quantitative assessments of disease responses (ie, using diffusion-weighted MRI [DW-MRI]) by characterizing the treatment-induced changes in tumor cell density. 17 Water-stable and homogeneously dispersed polyvinylpyrrolidone (PVP)-functionalized short SWCNTs that were further tagged with iron nanoparticles and conjugated with Endoglin/CD105 monoclonal antibody for specific targeting to tumor sites, were recently developed. 15 Coupling antibodyactive targeting with magnetic targeting by applying an external high-energy flexible magnet was found to improve the delivery of the magnetic SWCNTs to the tumor site in a murine breast cancer model.…”
Section: Introductionmentioning
confidence: 99%